2013
DOI: 10.1177/0884533613502813
|View full text |Cite
|
Sign up to set email alerts
|

Risks and Benefits of Prophylactic Cyclic Parenteral Nutrition in Surgical Neonates

Abstract: Background Cyclic parenteral nutrition (PN) is used for both the treatment and prevention of parenteral nutrition-associated liver disease (PNALD). Early initiation of prophylactic cyclic PN may not be well tolerated in young neonates. Our objective was to test the hypothesis that prophylactic cyclic PN initiated prior to the onset of hyperbilirubinemia is associated with younger age at initiation, lower bilirubin levels, and similar rates of adverse events compared to therapeutic cyclic PN initiated after est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Such difference might be explained by the fact that the PN initially administered in our hospital includes measures for the prevention of liver dysfunction, added to the fact that patients with a previous liver dysfunction were excluded from the study (15 patients). According to our protocol, these therapeutic measures must be adopted as soon as hepatic abnormalities are detected, which contradicts a recent study that suggests a benefit from early initiation of cPN [ 15 ]. Such measures include avoiding overfeeding, the early administration of enteral nutrition, the administration of cPN (8–12 h) [ 3 ], and the addition of taurine in PN.…”
Section: Discussionmentioning
confidence: 62%
“…Such difference might be explained by the fact that the PN initially administered in our hospital includes measures for the prevention of liver dysfunction, added to the fact that patients with a previous liver dysfunction were excluded from the study (15 patients). According to our protocol, these therapeutic measures must be adopted as soon as hepatic abnormalities are detected, which contradicts a recent study that suggests a benefit from early initiation of cPN [ 15 ]. Such measures include avoiding overfeeding, the early administration of enteral nutrition, the administration of cPN (8–12 h) [ 3 ], and the addition of taurine in PN.…”
Section: Discussionmentioning
confidence: 62%
“…Besides, interruption of PN in neonates could result in higher infection rate, possibly due to increased line handling [91,92]. A retrospective analysis of PN cycling in both preterm and term neonates with gastrointestinal disorders requiring surgical intervention showed that prophylactic daily discontinuous PN infusion could not prevent a rise in conjugated bilirubin concentrations [93]. In another retrospective analysis of PN treated neonates with gastroschisis, prophylactic cycling of all PN components was associated with reduced cholestasis but the association disappeared after adjusting for confounders [92].…”
Section: Continuous Vs Discontinuousmentioning
confidence: 99%
“…Children almost always tolerate night time infusion over 10e14 h [24]. The optimal time to initiate cyclical PN is unknown, and cycling may not be tolerated in young infants due to immature gluconeogenesis, limited glycogen stores, and large glucose demands [56]. However, there is evidence that cycling of PN is safe even in clinically stable newborns [56,57] (LoE 2À).…”
Section: Cyclical Pnmentioning
confidence: 99%